Cognitive emotion regulation strategies: A study of Iraqi ISIS survivors - Abd-alzim, Marwa (Journal of Indonesian Psychological Science (JIPS), 2025)
This study investigates the cognitive emotion regulation strategies applied by ISIS Iraq attack survivors in general and specific psychological results and effects of war-related trauma. This cross-sectional study intended to investigate gender and age differences in the use of maladaptive and adaptive coping strategies, utilizing the Cognitive Emotion Regulation Questionnaire-Arabic Version (CERQ-AR) among 420 survivors from Mosul, Iraq. Data were analyzed using confirmatory factor analysis (CFA), independent t-tests, and correlational analysis. Results showed that males scored significantly higher than females on rumination, catastrophizing, and other-blame. However, no gender difference was found in the case of adaptive strategies. The finding implies that these differences could be a function of the traditional gender roles in Iraqi society, especially in conservative areas like Mosul. Secondly, age as a variable in how these strategies are adopted: older individuals show a decline in maladaptive coping but an increase in other-blame. The research study ended with the recommendation that such cognitive emotion regulation strategies in post-conflict settings should be pursued through gender- and age-specific interventions. KEY WORDS: emotion regulation; ISIS survivors; war-related trauma; maladaptive coping; CERQ